2016
DOI: 10.1096/fj.201600280r
|View full text |Cite
|
Sign up to set email alerts
|

In β‐actin knockouts, epigenetic reprogramming and rDNA transcription inactivation lead to growth and proliferation defects

Abstract: EmiratesABSTRACT: Actin and nuclear myosin 1 (NM1) are regulators of transcription and chromatin organization. Using a genome-wide approach, we report here that b-actin binds intergenic and genic regions across the mammalian genome, associated with both protein-coding and rRNA genes. Within the rDNA, the distribution of b-actin correlated with NM1 and the other subunits of the B-WICH complex, WSTF and SNF2h. In b-actin 2/2 mouse embryonic fibroblasts (MEFs), we found that rRNA synthesis levels decreased concom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 49 publications
0
27
0
Order By: Relevance
“…We also found that immortalization induced by transformation with SV40 large T antigen rendered Actb nonessential for proliferation (Supplemental Figure S1). Although Tondeleir et al (2012) noted that cell survival was not impaired in their Actb-null MEFs immortalized by transformation with SV40 large T antigen, a more recent study reported a general delay in cell cycle progression, impaired colony growth, and reduced proliferation rate in the same cell line (Almuzzaini et al , 2016). Although we cannot exclude other effects of transformation with SV40 large T antigen, cell immortalization has been associated with substantial changes in gene expression (Kuo et al , 2012; Gordon et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…We also found that immortalization induced by transformation with SV40 large T antigen rendered Actb nonessential for proliferation (Supplemental Figure S1). Although Tondeleir et al (2012) noted that cell survival was not impaired in their Actb-null MEFs immortalized by transformation with SV40 large T antigen, a more recent study reported a general delay in cell cycle progression, impaired colony growth, and reduced proliferation rate in the same cell line (Almuzzaini et al , 2016). Although we cannot exclude other effects of transformation with SV40 large T antigen, cell immortalization has been associated with substantial changes in gene expression (Kuo et al , 2012; Gordon et al , 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear actin is also involved in transcription by all three eukaryotic RNA polymerases (12). Recent evidence indicates that b-actin binds to RNA polymerase I and serves as a molecular sink for recruitment of nuclear myosin 1 to the rRNA gene promoter-proximal enhancer (13). The absence of b-actin leads to growth and migration defects in cells (13,14).…”
mentioning
confidence: 99%
“…Recent evidence indicates that b-actin binds to RNA polymerase I and serves as a molecular sink for recruitment of nuclear myosin 1 to the rRNA gene promoter-proximal enhancer (13). The absence of b-actin leads to growth and migration defects in cells (13,14). Growing evidence has indicated that nuclear actin, together with nuclear myosin-1 has a general role in transcription (15) and that nuclear actin polymerization is necessary for the expression of factors in nuclear reprogramming, possibly through a chromatin-based mechanism (16,17).…”
mentioning
confidence: 99%
“…A report by Visa and Percipalle (2010) stated that β-actin has an essential role in gene expression as a component of chromatin modification complex. In gene expression, β-actin function was connected to RNA Polymerase I, II, and III (Almuzzaini et al, 2016;Serebryannyy, 2016); Hu et al, 2004). On the contrary, Ye et al (2008) stated that actin polymer deficiency will cause actin inability to bind with polymerase I, thus the transcription process is not supported.…”
Section: Discussionmentioning
confidence: 99%